Socio-community insights into the COVID-19 pandemic in the cities of Abidjan and Bouaké (Ivory Coast): Aperçus sociocommunautaires de la pandémie COVID-19 dans les villes d’Abidjan et de Bouaké (Côte d’Ivoire) (International Journal of Scientific Research and Management (IJSRM), 2021)
A pandemic that appeared in Wuhan in China considered in the early stages of the spread as the disease of others goes, by its virulent spread, to modify the mores of different human communities. Now, all of humanity is struggling for its survival as the most vulnerable continent surprises international opinion for its resilience while defeating the predictions of disasters. It is in this dispute that in Côte d’Ivoire, the taking in of this pandemic will experience two states. A clinical posture of curative and preventive regulation strongly represented in Abidjan while the localities of the interior escape the strictness of the provisions. As surprising as it may seem, COVID-19, which has become more visible among the Ivorian elite, will be weakly contracted and taken seriously by all communities. Although it is variously perceived by cultural areas, it still emerges a socially anchored resilience which nevertheless seems to be right in the spread of the pandemic. In a socio-anthropological approach, we will strive to elucidate the socio-community imaginaries that are the basis of the perception and community habits of COVID-19 in Côte d’Ivoire